2012
DOI: 10.1007/s00520-012-1465-0
|View full text |Cite
|
Sign up to set email alerts
|

Short post-infusion scalp cooling time in the prevention of docetaxel-induced alopecia

Abstract: A 45-min PICT can be recommended in 3-weekly docetaxel regimens with a dose of 75 or 100 mg/m(2), administered in 60 min. The shorter PICT is a major advantage in time investment for patients. Patients (women and men) who receive docetaxel, except combined with doxorubicin and cyclophosphamide (taxotere, adriamycin and cyclophosphamide (TAC)) should be informed about the protective effect and high tolerability of scalp cooling in avoiding CIA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 26 publications
1
53
0
3
Order By: Relevance
“…Nevertheless, SC should not be offered to patients with chemotherapy schedules in which chances of hair preservation are minimal;[21] Hair loss in spite of using SC causes an extra burden for patients and it tends to cause a deteriorated body image and quality of life. [2] Patient tolerance of SC was high and in accordance with the literature,[1422] but it was underestimated by nurses and MDs.…”
Section: Resultssupporting
confidence: 71%
See 2 more Smart Citations
“…Nevertheless, SC should not be offered to patients with chemotherapy schedules in which chances of hair preservation are minimal;[21] Hair loss in spite of using SC causes an extra burden for patients and it tends to cause a deteriorated body image and quality of life. [2] Patient tolerance of SC was high and in accordance with the literature,[1422] but it was underestimated by nurses and MDs.…”
Section: Resultssupporting
confidence: 71%
“…[24] However, CIA appeared to be an important side-effect of cancer treatment for males too[326] and, when SC was actively offered to them, 37%[22] to 57%[23] chose it. Again, this shows the need for improved information provision.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A subsequent study by the same authors found that a shorter post-infusion cooling time was as effective as a longer post-infusion cooling time (45 vs. 90 minutes). 72 …”
Section: Chemotherapy-induced Alopeciamentioning
confidence: 99%
“…107, 108 Although the ideal technique for cooling has yet to be elucidated, recent reports have yielded promising data regarding the optimal degree of cooling necessary 55 and the duration of post-infusion cooling. 72, 74 Further studies comparing different cooling techniques are needed. Finding more user-friendly means of providing effective scalp hypothermia would be helpful.…”
Section: Conclusion For Supportive Cryotherapymentioning
confidence: 99%